2012
DOI: 10.6061/clinics/2012(07)01
|View full text |Cite
|
Sign up to set email alerts
|

Renal macrophage infiltration is associated with a poor outcome in IgA nephropathy

Abstract: OBJECTIVES:The objectives of our study were as follows: 1) to analyze the prognostic value of macrophage infiltration in primary IgA nephropathy (IgAN) and 2) to study the relationship between macrophages and other factors associated with the development of renal fibrosis, including mast cells, TGF-β1, α-SMA and NF-kB.METHODS:We analyzed 62 patients who had been diagnosed with IgAN between 1987 and 2003. Immunohistochemical staining was performed with monoclonal antibodies against CD68 and mast cell tryptase a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
37
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 28 publications
0
37
0
Order By: Relevance
“…1 Kruskal-Wallis test: P < 0.0008 biopsies the receptor for the chemokine RANTES (CCRR5) was expressed by interstitial but not by glomerular macrophages [24]. A persistent high level of proteinuria is associated with severe histological lesions, including high scores of Oxford classification parameters [4,23,25,26]. In our study proteinuria levels did not correlate with histological findings.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…1 Kruskal-Wallis test: P < 0.0008 biopsies the receptor for the chemokine RANTES (CCRR5) was expressed by interstitial but not by glomerular macrophages [24]. A persistent high level of proteinuria is associated with severe histological lesions, including high scores of Oxford classification parameters [4,23,25,26]. In our study proteinuria levels did not correlate with histological findings.…”
Section: Discussionmentioning
confidence: 49%
“…Other authors have reported a correlation with impaired renal function at the time of biopsy and long-term prognosis [23]. In patients with C4d negative biopsies a high number of interstitial macrophages correlated with impairment of renal function at the time of biopsy and at the end of follow-up, whereas the number of glomerular macrophages did not have any functional or prognostic value.…”
Section: Discussionmentioning
confidence: 76%
“…Importantly, in both patients [4], [5], [8] and animal models [7], [9], [10], ROS have been shown to be involved in the progressive stage of IgAN, the most common type of primary glomerulonephritis. In addition, mononuclear leukocyte infiltration in the kidney of IgAN patients is highly implicated in converting IgAN into progressive renal injury [11][13]. These inflammatory mediators and pathways are considered a key step in IgAN prior to the development of chronic renal failure [11], [12], [14], [15].…”
Section: Introductionmentioning
confidence: 99%
“…IgA nephropathy (IgAN) is the most common primary glomerulonephritis and characterized by various degrees of intrinsic cell proliferation, especially mesangial cells (MCs), in the affected glomerulus, and mononuclear leukocyte infiltration in the glomerulus and renal interstitium1234, with insidious progression to end-stage renal disease in up to 50% of the patients56. Deposition of predominantly glomerular IgA immune complexes (ICs) or IgA immune aggregates167, and activation of innate immunity, followed by T cell activation and resultant inflammatory responses have been considered as a leading cause of the disease378.…”
mentioning
confidence: 99%